FTZ-F1, a steroid hormone receptor-like protein implicated in the activation of fushi tarazu. - Lavorgna, G.; Ueda, H.; Clos, J.; Wu, C. (Science, 1991)
The Drosophila homeobox segmentation gene fushi tarazu (ftz) is expressed in a seven-stripe pattern during early embryogenesis. This characteristic pattern is largely specified by the zebra element located immediately upstream of the ftz transcriptional start site. The FTZ-F1 protein, one of multiple DNA binding factors that interacts with the zebra element, is implicated in the activation of ftz transcription, especially in stripes 1, 2, 3, and 6. An FTZ-F1 complementary DNA has been cloned by recognition site screening of a Drosophila expression library. The identity of the FTZ-F1 complementary DNA clone was confirmed by immunological cross-reaction with antibodies to FTZ-F1 and by sequence analysis of peptides from purified FTZ-F1 protein. The predicted amino acid sequence of FTZ-F1 revealed that the protein is a member of the nuclear hormone receptor superfamily. This finding raises the possibility that a hormonal ligand affects the expression of a homeobox segmentation gene early in embryonic development.